2015
DOI: 10.1016/j.juro.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β1 Induced Urethral Fibrosis in a Rat Model

Abstract: TGF-β1 injection can successfully generate a reproducible rat model of urethral spongiofibrosis. This technique is simple, inexpensive and reproducible. Our series is a proof of concept study. Additional studies in larger animals are needed to further confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Based on our previously published study, we observed a number of TGF-β1 receptors in both human and rat urethras, and there was a significant increase in collagen type I and III expression following TGF-β1 injection in the same manner as in human urethral stricture specimens. 17 Furthermore, researchers have demonstrated that halofuginone, which is a specific inhibitor of TGF-β1 up-regulation, can prevent urethral fibrosis formation in rat urethra. 31,32 As such, we postulate this animal model to be suitable for our proof-of-concept study to evaluate the effects of ADSC injections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our previously published study, we observed a number of TGF-β1 receptors in both human and rat urethras, and there was a significant increase in collagen type I and III expression following TGF-β1 injection in the same manner as in human urethral stricture specimens. 17 Furthermore, researchers have demonstrated that halofuginone, which is a specific inhibitor of TGF-β1 up-regulation, can prevent urethral fibrosis formation in rat urethra. 31,32 As such, we postulate this animal model to be suitable for our proof-of-concept study to evaluate the effects of ADSC injections.…”
Section: Discussionmentioning
confidence: 99%
“…17 Briefly, each rat was anesthetized with 100 mg/kg ketamine (NWI Veterinary Supply, Boise, ID, U.S.) and 10 mg/kg xylazine (Akorn, Decatur, IL, U.S.) intraperitoneally. The rats were placed in the supine position.…”
Section: Urethral Injection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] Besides, TGF-β1 was proven to create fibrosis of the urethra in several animal studies. [25,26] These data may indicate a correlation between platelet counts and TGF-β1 levels.…”
Section: Discussionmentioning
confidence: 84%
“…In a multiinstitutional study Sangkum et al (page 820) developed a reproducible TGF-b1 injection technique to induce urethral fibrosis in the urethra of male rats. 3 In the experimental group TGF-b1 (5, 10 or 25 mg) was injected in each side of the urethral wall. Normal saline infiltration was used in the sham treated group.…”
Section: Transforming Growth Factor-b1 Induced Urethral Fibrosismentioning
confidence: 99%